Violencias, grupos vulnerables y deserción escolar. Análisis para su comprensión, incidencia y transformación social. - Juárez Lozano, Ricardo (2024)
The main objective of the research project “Violence, vulnerable groups and school dropout” is to understand structural violence, reduce school dropout and promote a culture of prevention in the community of Valle de Juárez, specifically in the Miguel Ahumada # 2289 elementary school. The aim is to identify the causes of these phenomena and propose interventions to improve the social and educational situation in the region. The research is structured around three axes: vulnerable groups, school dropout and prevention culture. Using an ethnographic approach, techniques such as bibliographic review, semi-structured interviews, focus groups and participant observation will be used for data collection. The project, which will be developed in several stages, will begin with a diagnosis and analysis of the context, and will be followed by immersion in the field and the collection of specific data. In addition, training workshops will be held for teachers and parents to strengthen their skills and promote their participation in the change process. The project's results are expected to have a positive impact on children, young people and their families, contributing to a safer and healthier environment. In the long term, the project seeks to establish an intervention model that can be replicated in other vulnerable communities in the country, promoting a culture of peace and prevention.